Предмет: Алгебра, автор: smith61

Найдите производную срочно! 75 баллов! ​

Приложения:

Ответы

Автор ответа: Miroslava227
1

Ответ:

1)f'(x) =  \frac{3 \times 6}{4}  {x}^{5}  - 6 {x}^{ - 4}  -  \frac{1}{4}  \times  \frac{1}{2}  {x}^{ -  \frac{1}{2} }  =  \\  =  \frac{9}{2}  {x}^{5}  -  \frac{6}{ {x}^{4} }  -  \frac{1}{8 \sqrt{x} }

2)f'(x) =  \frac{7}{3}  \times 3 {x}^{2}  - 3 {x}^{  - 2}  =  \\  = 7 {x}^{2}  -  \frac{3}{ {x}^{2} }

3)f'(x) = 1 \times (x + 2) + 1 \times (x - 8) = 2x - 6

4)f'(x) =  \frac{1 \times (x - 4) - 1 \times (x + 5)}{ {(x - 4)}^{2} }  =  \\  =  \frac{x - 4 - x - 5}{ {(x - 4)}^{2} }  =   - \frac{9}{ {(x - 4)}^{2} }

5)f'(x) = 3 {x}^{2} (2x + 3) + 2( {x}^{3}  - 1) = \\  =  6 {x}^{3}  + 9 {x}^{2}  + 2 {x}^{3}  + 2 = 8 {x}^{3}  + 9 {x}^{2}  + 2

6)f'(x) =  \frac{(2x + 2) {x}^{3}  - 3 {x}^{2}( {x}^{2} + 2x - 3)  }{  {x}^{6}  }  =  \\  =  \frac{2 {x}^{4}  + 2 {x}^{3}  - 3 {x}^{4}  - 6 {x}^{3} +  {x}^{2}  }{  {x}^{6}  }  =  \\  =   \frac{ -  {x}^{4} - 4 {x}^{3} +  {x}^{2}   }{ {x}^{6} }  =  \frac{ {x}^{2}(1 -  {x}^{2} - 4x)  } { {x}^{6}  }  =  \\  =  \frac{1 -  {x}^{2} - 4x }{ {x}^{4} }

7)f'(x) =  \frac{1}{2}  {(3 {x}^{2}  - 8x)}^{ -  \frac{1}{2} }  \times (6x - 8) = \\  =   \frac{2(3x - 4)}{2 \sqrt{3 {x}^{2} - 8x } }  =  \frac{3x - 4}{ \sqrt{3 {x}^{2} - 8x } }

8)f'(x) = 4 {x}^{3}  - 15 {x}^{2}

9)f'(x) = 2x(3x - 7) + 3( {x}^{2}  - 1) =  \\  = 6 {x}^{2}  - 14x + 3 {x}^{2}  - 3 =  \\  = 9 {x}^{2}  - 14x - 3

10)f'(x) = 6 {x}^{7}  - 6 {x}^{ - 3}  -  \frac{1}{6}  \times  \frac{1}{2}  {x}^{ -  \frac{1}{2} }  =  \\  = 6 {x}^{7}  -  \frac{6}{ {x}^{3} }  -  \frac{1}{12 \sqrt{x} }

11)f'(x) =  \frac{(3 {x}^{2}  - 4)x - ( {x}^{3} - 4x + 3) }{ {x}^{2} }  =  \\  =  \frac{3 {x}^{3} - 4x -  {x}^{3} + 4x - 3  }{ {x}^{2} }  =  \\  =  \frac{2 {x}^{3} + 3 }{ {x}^{2} }

12)f'(x) =  \frac{13}{3}  \times 3 {x}^{2}  -  {x}^{ - 2}  =  \\  = 13 {x}^{2}  -  \frac{1}{ {x}^{2} }

13)f'(x) =  \frac{1}{2}  {(8 + 4x)}^{ -  \frac{1}{2} }  \times 4  = \\  =  \frac{2}{ \sqrt{8 + 4x} }

14)f'(x) = x + 1 + x - 5 = 2x - 4

15)f'(x) =  \frac{1}{2 \sqrt{3 {x}^{2}  - 8x} }  \times (6x - 8) =  \\  =  \frac{3x - 4}{ \sqrt{3 {x}^{2}  - 8x} }

16)f'(x) =  \frac{2(x - 4) - (2x + 5)}{ {(x - 4)}^{2} }  =  \\  =  \frac{2x - 8 - 2x - 5}{ {(x - 4)}^{2} }  =  \\  =  -  \frac{13}{ {(x - 4)}^{2} }

17)f'(x) = 1 \times  \sqrt{3 - 4 x}  +  \frac{1}{2}  {(3 - 4x)}^{ -  \frac{1}{2} }  \times ( - 4) \times x =  \\  =  \sqrt{3 - 4x}  -  \frac{2x}{ \sqrt{3 - 4x} }

Похожие вопросы
Предмет: Русский язык, автор: bobrovka1